Teachers’ Elementary School in Online Learning of COVID-19 Pandemic Conditions - Irfan Fauzi; Iman Hermawan Sastra Khusuma (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
The article aimed to explain in detail the perspectives of elementary school teachers about online learning in a COVID-19 pandemic condition. This study used a quantitative approach. The subjects in this study were 45 teachers in Banten and West Java. The results of this study indicated that teachers understand the context of online learning, but in implementation there are various problems found, including 1) availability of facilities, 2) network and internet usage, 3) planning, implementation, and evaluation of learning, and 4) collaboration with parents. Online learning help teachers in the COVID-19 pandemic period, but felt to be ineffective, even 80% of teachers feel dissatisfied thorough online learning. This research was expected to be an evaluation material for various parties including education policy makers in conducting online learning, besides this research can also facilitate other researchers to develop research on online learning, especially in elementary schools. Keywords: Online Learning, COVID-19 Pandemic, COVID-19